Peran Stakeholder Pada Kegiatan Pengendalian Organisme Pengganggu Tanaman Padi Secara Hayati Oleh Kelompok Tani Sedyo Rukun Kapanewon Bantul - Dhamayanti, Crisnha Sari (Journal of Agricultural Social and Business, 2025)
This study aims to examine the role of stakeholders in the implementation of biological pest control activities for rice plants by the Sedyo Rukun Farmer Group. This research is qualitative research with a case study method, using primary and secondary data sources, with data collection techniques through interviews, observation, documentation, then data validity with source triangulation. Data analysis techniques by collecting data, reducing data, presenting data and drawing conclusions. The results showed that stakeholders consisting of the Bantul Regency DKPP and the Sabdodadi Village Government play a role in providing facilities to farmers, but have not yet reached the stage of providing power so that biological pest control activities for rice in the Sedyo Rukun Farmers Group have not yet sustainable